Cellulose Acetate‐Based High‐Electrolyte‐Uptake Gel Polymer Electrolyte for Semi‐Solid‐State Lithium‐Oxygen Batteries with Long‐Cycling Stability. Issue 21 (19th September 2022) - Xu, Zelin; Guo, Dingcheng; Liu, Ziqiang; Wang, Zhiyan; Gu, Zhi; Wang, Da; Yao, Xiayin
Abstract: Lithium‐oxygen batteries have received great research interest owing to their ultrahigh theoretical energy density and are considered as one of the promising secondary batteries. However, there are still some challenges in their practical application, like liquid organic electrolyte evaporation in the semi‐open system and instability in the high‐voltage oxidizing environment. In this work, a cellulose acetate‐based gel polymer electrolyte (CA@GPE) is proposed, whose cross‐linked microporous structure ensures the ultrahigh liquid electrolyte uptake of 2391%. The prepared CA@GPE exhibits a high lithium‐ion transference number of 0.595, a satisfying ionic conductivity of 0.47 mS cm −1 and a wide electrochemical stability window up to 5.0 V. The Li//Li symmetric cell employing CA@GPE could cycle stably over 1200 h. The lithium‐oxygen battery with CA@GPE presents a superb cycling lifetime of 370 cycles at 0.1 mA cm −2 under 0.25 mAh cm −2 . This work offers a possible strategy to realize long‐cycling stability lithium‐oxygen batteries. Abstract : A semi‐solid‐state cellulose acetate‐based gel polymer electrolyte (CA@GPE) with an ultrahigh liquid electrolyte uptake of 2391% is proposed to relieve the leakage and volatility of liquid organic electrolytes in the semi‐open system of lithium‐oxygen batteries at ambient temperature. The lithium‐oxygen battery with CA@GPE exhibits excellent long‐cycling stability as well as superior reversibility.